THE INTERRELATIONSHIP OF PAINTING AND SOCIETY - YESTERDAY AND TODAY - Mahobe, Yatindra (International Journal of Research -GRANTHAALAYAH, 2026)
Art has been a powerful medium of expression since the dawn of human civilization and has maintained a deep and inseparable relationship with society. The topic “The Interrelationship Between Art and Society – Then and Now” clearly establishes that art is not merely an expression of beauty, but a vivid reflection of society’s culture, traditions, beliefs, ideologies, and social transformations. From prehistoric cave paintings to modern and contemporary digital art, the art of every era has continuously reflected the social realities of its time. In ancient times, the primary purpose of art was the depiction of religious faith, social morality, and collective life. Cave paintings of Bhimbetka, Ajanta–Bagh murals, and temple art traditions portray the lifestyle, spiritual consciousness, and cultural values of contemporary society. During the medieval period, Mughal, Rajput, and folk painting styles depicted themes of royalty, love, war, daily life, and religious sentiments, providing a clear understanding of the social structure and prevailing ideologies of that era. In the modern period, the nature of art changed alongside social, political, and economic transformations. Colonial influence, education, and globalization provided new perspectives to art. In modern and contemporary art, artists have focused on issues such as social inequality, women empowerment, environmental crises, identity, and human emotions. Digital media and new technologies have further connected art with a broader segment of society. This research abstract clearly establishes that while art is influenced by society, it also influences society in return. The art of the past served as a carrier of tradition and collective consciousness, whereas contemporary art has become an expression of social issues, struggles, and change. Thus, the interrelationship between art and society remains continuous, dynamic, and ever-evolving, playing a significant role in the development of human civilization.